Rancang Bangun Monitoring Kekeruhan dan Padatan Terlarut pada Air Sungai - pambudi prasetyo (Politeknik Negeri Malang, 2019)
Water is a very basic need in the survival of all living things. The limited amount of clean water and the increasing human growth rate in Indonesia are slowly starting to cause a clean water crisis. Apart from the quantity, the fresh water quality is getting worse. The increasing need is directly proportional to the increasing exploitation of springs, but in fact it's inversely proportional to public awareness of the need for treatment, care and monitoring of river conditions, especially for people in urban, industrial and densely populated areas. In this research, it is proposed a design design for river water monitoring devices using the internet of things method with a media monitor and a public website-based interface that can be accessed by anyone who wants to know about updated river condition information. There are two observation parameters in this study, including dissolved liquid solids content (PPM) and liquid turbidity (NTU), which changes will be observed with the river prototype media in a paralon pipeline. The data received by the sensor is then processed by the Wemos D1 microcontroller and sent to an online database to be displayed in the form of graphs or data records or tables. From the implementation of this research, it is hoped that the community around the watershed can obtain information about the impact of activities around the river on water conditions and quality. With that, it's hoped that the community will have more awareness of the importance of togetherness in protecting the surrounding rivers.